2010
DOI: 10.1021/la103689m
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid-Induced Unprecedented Size Enhancement of Aggregates within Aqueous Sodium Dodecylbenzene Sulfonate

Abstract: Physicochemical properties of aqueous micellar solutions may change in the presence of ionic liquids (ILs). Micelles help to increase the aqueous solubility of ILs. The average size of the micellar aggregates within aqueous sodium dodecylbenzene sulfonate (SDBS) is observed by dynamic light scattering (DLS) and transmission electron microscopy (TEM) to increase in a sudden and drastic fashion as the IL 1-butyl-3-methylimidazolium hexafluorophosphate ([bmim][PF(6)]) is added. Similar addition of [bmim][PF(6)] t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 35 publications
(16 reference statements)
6
43
0
Order By: Relevance
“…The obtained value of the hydrody namic diameter of SDBS micelles is 4.2 nm. This agrees rather well with the results from [15,20,21] and is in the range of values characteristic for spherical micelles [8].…”
Section: Studies Of Micellar Mgcr 8 Pc-sdbs Solutionssupporting
confidence: 91%
“…The obtained value of the hydrody namic diameter of SDBS micelles is 4.2 nm. This agrees rather well with the results from [15,20,21] and is in the range of values characteristic for spherical micelles [8].…”
Section: Studies Of Micellar Mgcr 8 Pc-sdbs Solutionssupporting
confidence: 91%
“…32 They may be size-enhanced micelles which are similar to those reported in literature. 20,33,34 Additional DLS analyses have been carried out at a fixed mass ratio of [C 2 pi][BF 4 ]/SDS of 7:5, and the results are presented in Figure 7. The samples were measured at the same time as soon as prepared.…”
Section: Resultsmentioning
confidence: 99%
“…20,33,34 In the latter situation, one example is the work reported by Rai et al, who discussed the size enhancement of aggregates in the aqueous solution mixed with imidazolium-based IL and SDS or SDBS. 33 They observed that the size of aggregates increased much more in the IL + SDBS + water system than that in the IL + SDS + water system, which was mainly attributed to the benzene ring in SDBS and the generated cation−π interaction. To get a more comprehensive understanding of the microstructures of the ATPS in this work, different structural models are proposed for the ATPS under study.…”
Section: Resultsmentioning
confidence: 99%
“…Pandey et al have shown the effect of ILs on the aggregation behavior of different types of surfactants [23][24][25]. Inoue's group has highly explored the effect of ILs on aggregation of polyoxyethylene (POE)-type non-ionic surfactants [26,27].…”
Section: Introductionmentioning
confidence: 99%